PENGGUNAAN PARAMETER VEGETASI DALAM MENENTUKAN TINGKAT KEBERHASILAN REKLAMASI - Rahmat Hapizil Islami; Luthfi Fatah; Kissinger Kissinger; Badaruddin Badaruddin (EnviroScienteae, 2023)
Mining activities in forest areas are carried out by granting borrow-to-use permits for forest areas by taking into account area limitations and certain time periods as well as environmental sustainability. Problems caused after mining include infertile soil, acidic pH, and low nutrients. These problems can be overcome by reclamation activities to improve and restore land functions to a better and more productive condition. Reclamation activities carried out include land arrangement, erosion and sedimentation control, and revegetation (Ministry of Forestry, 2009). The approach used in this study is descriptive quantitative, with a research implementation time of 6 (six) months. The object of this study is the object of this study is the assessment of reclamation and revegetation in the 2016 and 2017 planting years at PT. Binuang Mitra Bersama in Block 1 and PT. X in Block 4 based on Minister of Forestry Regulation No. P.60/Menhut-II of 2009 concerning Guidelines for Evaluating the Success of Forest Reclamation and Decree of the Minister of Energy and Mineral Resources Number 1827K/30/MEM/2018 of 2018 concerning Guidelines for Implementing Good Mining Engineering Principles. The results of the assessment of the success rate of reclamation based on the parameters of revegetation according to KEPMEN ESDM NO. 1827 K/30/MEM/ 2018 for PT. BMB reached 66.19% or good criteria, for the percentage of plant growth was 85%, included in the good category with 80% planting local types of plants and PT.X reached 57.62% or not good criteria because the results of the assessment of planting cover crops were only 0 .5%, planting fast growing plants is only 2% and planting local plant species is only 1%. While the results of the assessment of the success rate of reclamation are based on the parameters of revegetation according to the Minister of Forestry Regulation no. P.60/Menhut-II Year 2009 for PT. BMB reaches 75% with a good success rate, for planting indicators with 4 (four) parameters weighing 4 (four) values and 1 (one) parameter weighing 1 (one) because the presentation is only 33.86% categorized as reclamation <60%, this because there are still temporary residential buildings and places for standby equipment for excavators and PT.X, the plant health value reaches 55%, the success rate is included in the bad category.